2009
DOI: 10.1002/rcm.3981
|View full text |Cite
|
Sign up to set email alerts
|

A mass spectrometry based imaging method developed for the intracellular detection of HIV protease inhibitors

Abstract: Mass spectrometry imaging is a promising technique for measuring drugs and drug metabolites in cells and tissues. In this manuscript we describe a method for the imaging of HIV protease inhibitors. As a model system we used Mono Mac 6 cells cultured with the HIV protease inhibitors saquinavir and nelfinavir deposited on glass slides using a cytocentrifuge. A sublimation/deposition device for homogeneous matrix deposition was constructed which allows imaging of these HIV protease inhibitors at clinically releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 14 publications
(12 reference statements)
0
34
0
Order By: Relevance
“…Homogeneous thin microcrystal layers can be obtained by a thermal vapor deposition of matrix (Kim, Shin, & Yoo, 1998;Hankin, Barkley, & Murphy, 2007;Dekker et al, 2009). Dekker et al (2009) use an in-house built sublimation/deposition device to deposit 2,5-DHB onto cytocentrifuged cells that were cultured in the presence of HIV protease inhibitors (see Fig.…”
Section: B Increasing Homogeneous Sample/ Matrix Crystallizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Homogeneous thin microcrystal layers can be obtained by a thermal vapor deposition of matrix (Kim, Shin, & Yoo, 1998;Hankin, Barkley, & Murphy, 2007;Dekker et al, 2009). Dekker et al (2009) use an in-house built sublimation/deposition device to deposit 2,5-DHB onto cytocentrifuged cells that were cultured in the presence of HIV protease inhibitors (see Fig.…”
Section: B Increasing Homogeneous Sample/ Matrix Crystallizationmentioning
confidence: 99%
“…Dekker et al (2009) use an in-house built sublimation/deposition device to deposit 2,5-DHB onto cytocentrifuged cells that were cultured in the presence of HIV protease inhibitors (see Fig. 3).…”
Section: B Increasing Homogeneous Sample/ Matrix Crystallizationmentioning
confidence: 99%
“…Matrix deposition by sublimation has proven reliable for a variety of applications in the MALDI imaging field [19,22,23,28,38,39]. Conventional sublimation apparatuses for bulk chemical purification provide limit-ed control over thickness and in-plane uniformity of the matrix deposited.…”
Section: Thin Layer Transfer (Tlt)mentioning
confidence: 99%
“…DD leads to non-uniform analyte/matrix co-crystallization forming "sweet spots" which reduce inter-and intra-assay reproducibility [14][15][16]. Alternative matrix deposition methods have been reported to enhance homogeneity of matrix/analyte co-crystals [17][18][19][20][21][22][23][24][25][26][27][28], although MALDI-TOF measurements typically yield precisions above 20 % relative standard deviation (RSD). Performing relative quantitation against an internal standard at similar molecular mass to the target analyte improves MALDI precision to G10 % RSD [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Using this technique, a matrix can be applied uniformly over a large sample plate in a few minutes without solvents. Additionally, previous reports demonstrated that this method increases analyte signal and that the fine microcrystals formed from the condensed vapor reduce the image resolution limitation caused by crystal size (Dekker et al, 2009;Vrkoslav et al, 2010).…”
Section: Matrix Applicationmentioning
confidence: 96%